2014
DOI: 10.3844/ajabssp.2014.342.360
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Rhizobia and Plant Growth-Promoting Rhizobacteria and Their Effects on Growth of Rice Seedlings

Abstract: Biofertilizer is a relatively safer, environmentally friendly and cost-effective approach as an alternative to reduce chemical fertilizer usage. The selection of bacterial strains with multiple beneficial characteristics are important to maximize the effectiveness on the host plant. Due to aforementioned interest, several Plant Growth-Promoting Rhizobacterial (PGPR) and rhizobial strains were isolated from rice and legume roots, respectively, at four locations in Malaysia namely Universiti Putra Malaysia (UPM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 67 publications
5
29
1
2
Order By: Relevance
“…Although rhizobia are recommended for biological N fixation in nodule-forming Fabaceae species, they can act as growth promoters in other plant species, including Poaceae, such as maize. Tan et al (2014) observed greater growth of rice through the action of different species of rhizobacteria, including those of the genus Rhizobium.…”
Section: Resultsmentioning
confidence: 99%
“…Although rhizobia are recommended for biological N fixation in nodule-forming Fabaceae species, they can act as growth promoters in other plant species, including Poaceae, such as maize. Tan et al (2014) observed greater growth of rice through the action of different species of rhizobacteria, including those of the genus Rhizobium.…”
Section: Resultsmentioning
confidence: 99%
“…: no significant differences importance for increasing the competitiveness of the plants under study, under field conditions. Other authors also observed stimuli in the initial establishment phase of plants inoculated with rhizobia (Vargas et al, 2009;Stroschein et al, 2011;Tan et al, 2014), which is important interaction on growth and early crop development.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, rhizobia have also been reported to enhance the growth and yield of non-legumes e.g. wheat (Mehboob et al, 2011), rice (Tan et al, 2014), maize (Hadi and Bano, 2010) etc. Rhizobial isolates colonize roots of non-legumes and enhance plant growth by several direct and indirect mechanisms of action.…”
Section: Inoculation With Rhizobial Consortium For Improving the Growmentioning
confidence: 99%